Excretory/secretory proteins inhibit host immune responses by downregulating the TLR4/NF-κB/MAPKs signaling pathway: A possible mechanism of immune evasion in parasitic nematode Haemonchus contortus - Wen, Zhaohai; Zhang, Yue; Feng, Jiajun; Aimulajiang, Kalibixiati; Aleem, Muhammad Tahir; Lu, Mingmin; Xu, Lixin; Song, Xiaokai; Li, Xiangrui; Yan, Ruofeng (Frontiers in Immunology, 2022)
Haemonchus contortus is an important parasitic nematode of ruminants. Previous studies showed that H. contortus escape the immunity through complex mechanisms, including releasing excretory/secretory proteins (ESPs) to modulate the host immune response. However, the detailed mechanism through which H. contortus excretory/secretory proteins (HcESPs) promote immune evasion remains unknown. In the present study, we demonstrated that HcESPs inhibit the adaptive immune response of goats including downregulation of immune cell antigen presentation, upregulation of immune checkpoint molecules, activation of the STAT3/PD-L1 pathway, and activation of immunosuppressive regulatory T (Treg) cells. Furthermore, HcESPs reversed the LPS-induced upregulation of pro-inflammatory mediators in PBMCs by inhibiting the TLR4/NF-κB/MAPKs/NLRP3 signaling pathway. Our study provides a better understanding of the evasion mechanisms for H. contortus, which could be helpful in providing an alternative way to prevent the infection of this parasite.